Association of Fine Particulate Matter and Residential Greenness With Risk of Pulmonary Tuberculosis Retreatment: Population-Based Retrospective Study - Tonglei Guo; Fei Shen; Henan Xin; Jiang Du; Xuefang Cao; Boxuan Feng; Yijun He; Lingyu Shen; Yuanzhi Di; Yanxiao Chen; Zihan Li; Qi Jin; et al. (JMIR Public Health and Surveillance)
Abstract BackgroundThe evidence on the association of fine particulate matter with an aerodynamic diameter of 2.5 μm or less (PM2.5 ObjectiveIn a population-based retrospective study, we aimed to investigate the influence of PM2.5 MethodsA total of 26,482 patients with incident PTB, registered in a mandatory web-based reporting system between 2012 and 2019 in Zhengzhou, China, were included in the analysis. The exposure to PM2.52.5 ResultsAmong the 26,482 patients (mean age 46.86, SD 19.52 years) with a median follow-up time of 1523 days per patient, 1542 (5.82%) PTB retreatments were observed between 2012 and 2019. Exposure to PM2.532.52.5 ConclusionsLong-term exposure to PM2.5